2020
DOI: 10.1016/j.psj.2020.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lysine and methionine in a low crude protein diet on the growth performance and gene expression of immunity genes in broilers

Abstract: Globally, the poultry industry is 1 of the most advanced livestock industries. Feed contributes to the biggest proportion (65–70%) of the production cost. Most feed ingredients in Malaysia are imported, which contributes to the high food bill annually, and alternative feed formulation may help decrease the cost of poultry feed. Feed formulation are improved to efficiently meet the dietary requirements of the broilers and 1 of the ways is by reducing the level of crude protein in the diet while supplementing es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 39 publications
(46 reference statements)
1
17
0
1
Order By: Relevance
“…In the present study, serum proline and lysine were lowest in the LPR group, consistently lower than in the LPM group. The lower serum proline and lysine may explain why the growth performance was the weakest in the LPR group since lysine ( Jespersen et al, 2021 ) is vital in promoting poultry growth ( Lee et al, 2020 ). Our data demonstrated that the proline might be essential in promoting growth in goslings fed with low-protein diets.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, serum proline and lysine were lowest in the LPR group, consistently lower than in the LPM group. The lower serum proline and lysine may explain why the growth performance was the weakest in the LPR group since lysine ( Jespersen et al, 2021 ) is vital in promoting poultry growth ( Lee et al, 2020 ). Our data demonstrated that the proline might be essential in promoting growth in goslings fed with low-protein diets.…”
Section: Discussionmentioning
confidence: 99%
“…In attempt to better understand the positive effects of dietary Ser addition on the performance of birds fed LCP diets, the expression of some important genes related to ileal mucosal immunity was further investigated. Mucins are the main component of the intestinal mucus layer, whose main function is to protect the intestine from the hostile external elements (chemical, physical, or bacterial) as a form of innate immunity in poultry ( Erf, 2004 ; Lee et al., 2020 ). MUC2 is a typical secreted mucin, and any dietary changes may influence its expression and function in the intestinal mucus layer ( Linden et al., 2008 ; van der Sluis et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that no significant difference in weight gain was observed in geese with dietary protein levels ranging from 16 to 22%, which seems overly general in scope ( Summers et al, 1986 ). Conversely, the concentrations of dietary protein exert a strong effect on intestinal flora balance and disease resistance in poultry ( Lee et al, 2020 ). Visceral gout, which occurs mainly in birds, is a metabolic disease caused by impaired kidney function, followed by an accumulation of urate crystals in various organs ( Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%